ANALISIS SIKAP KONSUMEN TERHADAP ATRIBUT PRODUKPINDANG PRESTO MURTADHOPURWOREJO (STIE Rajawali Purworejo, 2018)
The purpose of this study is to determine consumer attitudes toward the attribute pindang presto Murtadho in terms of revenue. Pies attribute presto Murtadho namely: product attributes and price attributes. While the characteristics of consumers in this study based on the level of consumer income is divided into four groups, namely: (1) (<-Rp 500.000), (2) (Rp 500,000-Rp1,000,000), (3) (Rp 1,000,000-Rp 1,500,000) and (4) (>-Rp 1,500,000).The result of the research shows that the attitude of fishbein is obtained by the attitude value of whole (Ao) equal to 4,09, where the value is located in the reception area is very confident, that means the consumer can accept the product attribute and the price attribute at pindang presto murtadho business. Chi-Squaretest result that there is no difference of consumer to product attribute and prestopresto price attribute Murtadho in terms of consumer's income.Keyword: , product attributes and price attributes